UI/UX Design of a Decision Support System to Determine Lecturer Research Linearity using the Design Thinking Method - Nugroho, Ahmad; Narulita, Siska; Abdillah, M. Zakki (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The goal of this study is to develop a prototype UI/UX Decision Support System for Determining Lecturer Research Linearity based on user needs, in which users can manage research data, determine the suitability of research conducted by lecturers with their scientific fields, provide a basis for decision-making in determining whether lecturer research should be continued, and provide an overview to decision-makers regarding lecturer performance. This study used the design thinking technique, which is divided into five stages: obtaining information from users, analyzing user needs, generating ideas for solutions to user problems, creating prototypes to solve user problems, and testing and improving prototypes. This study successfully created a decision support system design and prototype that is centered on user demands and comfort. Prototype testing was carried out by UI/UX design experts. The test findings demonstrate that users respond positively to the decision support system interface and that most functionalities work properly. This demonstrates that the decision support system prototype was created with user demands, functional suitability, and convenience of use in mind. The findings of this study are expected to be used in associated institutions or agencies to collect feedback for future system improvement.